PENGARUH KONSEP DIRI DAN KETAATAN BERIBADAH TERHADAP KESALEHAN SOSIAL SISWA DI MADRASAH TSANAWIYAH KOTA PEKANBARU - Anisatul Umah; Mas’ud Zein; Khairil Anwar (STAI Nurul Falah Airmolek, 2024)
This study aims to determine the influence of self-concept on social piety, the influence of obedience in worship on social piety, and the influence of self-concept and obedience in worship on the social piety of students at Islamic Junior High School in Pekanbaru City. This research is a field study with a quantitative approach. The research sample consists of 271 students at Islamic Junior High School in Pekanbaru City. The data analysis technique uses linear and multiple regression. The results of this study show that self-concept has a significant influence on the social piety of of students at Islamic Junior High School in Pekanbaru City. This is indicated by the result where the calculated r value is greater than the r table (0.678 > 0.119) with a significance value of 0.000 < 0.05, contributing 40.7%. Obedience in worship has a significant influence on the social piety of of students at Islamic Junior High School in Pekanbaru City. This is indicated by the result where the calculated r value is greater than the r table (0.208 > 0.119) with a significance value of 0.001 < 0.05, contributing 4.3%. There is a significant simultaneous influence of self-concept and obedience in worship on the social piety of students at Islamic Junior High School in Pekanbaru City. This is indicated by an F value (96.944 > 3.03), contributing 42%. This means that the independent variables contribute 42% to the dependent variable.